Will China's water resources be safe in 2030? - Lishuo Guo; Lifang Wang (Water Policy, 2021)
This paper is distinct from existing studies on water resources carrying capacity which usually use dimensionless data to represent trend and status of water resources carrying capacity. Here, on the grounds of the most stringent water resource management system and following the principles of water determining population, water determining city scale, water determining production and so on, water resources carrying capacity prediction model was established. The water resources carrying capacity was represented by population, which can directly reflect the status of water resources. Under the rigid constraints of water use quantity and water use efficiency, six scenarios were set to predict China's maximum population in 2030. The results demonstrated that the maximum population in each scenario is close to 1.45 billion of National Population Development Plan. It means water resources rigid constraints can support population and economic growth at the socio-economic development current pace and path. Total water use quantity will not break through the limit of 800–900 billion m3 when achieving the expected goals of social and economic development, not even more than 700 billion m3. Meanwhile, in order to relieve water resources stress, to improve water resources carrying capacity, and to accelerate construction of a water-saving society, some suggestions were put forward. Highlights Constructed water resource carrying capacity model with population as objective function is used to evaluate future water security.; The maximum population is estimated under 700 billion cubic meters of total water use control line.; By 2030, total water use quantity will never come to its limit, not even more than 700 billion cubic meters.;